Five models for European security : implications for the United States - Gantz, Nanette C.; Steinberg, James, 1951-; Arroyo Center. Strategy and Doctrine Program; Rand Corporation; United States. Army. (Santa Monica, CA : RAND, 1992)
This Note assesses five alternative security models that could emerge in the next 5-10 years in terms of how well they meet the U.S. objective of transnational stability in Europe. The Note finds that of the five models proposed, the overlapping security institutions model does best, because it preserves a political and military role for the United States, creates alternative links for U.S. involvement in Europe beyond NATO, demonstrates U.S. willingness to adapt to a stronger European role in security arrangements, and maintains flexibility to move to a number of different security models. The Note recommends that the United States develop a credible rationale for maintaining an integrated military command like NATO, encourage the expansion of the Western European Union's role as a bridge between NATO and the European Community, support the process of European economic and political integration, and encourage the use of the Conference on Security and Cooperation in Europe as a pan-European forum for addressing the security concerns of the newly emerging democracies in the East.
Research "conducted within the Strategy and Doctrine Program of RAND's Arroyo Center"--Preface.
Includes bibliographical references.
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: National security -- Europe; Political stability -- Europe; Europe -- Military relations -- United States; United States -- Military relations -- Europe